THE ENHANCEMENT OF ENGLISH TRAININGS FOR LECTURERS IN ENGLISH PRACTICUM CLASS - Sri Wahyuningsih (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
This paper attempts at exploring some strategies used to improve the lecturers’ competence and facilities supporting the process of teaching English as well as the better outputs from English Practicum Class. The research belongs to a descriptive qualitative research. The interview and observation were done to gather data. The result showed that there are a number of programs designed and conducted by the chief and team of the language development unit (UPB) to enhance the competence of lecturers in English Practicum Class. These programs cover compiling a workbook of English Intensive Program “Have Fun with English”, conducting the International Conference and Call for Papers, providing Academic Writing Course for lecturers, training of TOEFL Test, training of English item test methodology, etc. In fact, some lecturers in English practicum class enthusiastically participate in such programs.DOWNLOAD ABSTRACT